2018
DOI: 10.1523/jneurosci.1702-17.2018
|View full text |Cite
|
Sign up to set email alerts
|

The Lifespan Trajectory of the Encoding-Retrieval Flip: A Multimodal Examination of Medial Parietal Cortex Contributions to Episodic Memory

Abstract: The formation of episodic memories is associated with deactivation during encoding and activation during retrieval in the posteromedial cortex (PMC). We hypothesized that the encoding/retrieval (E/R) flip is a critical component of episodic memory across the lifespan because structural and metabolic changes in the PMC coincide with the fine tuning of the episodic memory system in development and the reductions of memory performance in aging. The aims of the present study were, first, to describe lifespan traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 90 publications
2
11
0
Order By: Relevance
“…Overall this suggests that age-related deficits in the brain activity associated with memory retrieval can drive lower asymmetry in older brains. This is in line with the well-established view that aging is associated with the dedifferentiation of previously specialised neural systems (Park et al 2004(Park et al , 2012Park and McDonough 2013;Koen et al 2019), and may also reconcile well with studies demonstrating that the regionally-dependent dynamic range of activity available to older adults may be lower across varying task conditions (Garrett et al 2011(Garrett et al , 2013Kennedy et al 2017;Amlien et al 2018), a potential alternative account that may explain findings of lower-toabsent negative memory effects in older adults (Mattson et al 2014;de Chastelaine et al 2015). In particular, our finding that absent negative effects explained all instances of apparent over-activation in older adults agrees well with a similar report during retrieval (Morcom et al 2007).…”
Section: Age-related Differences In Asymmetrysupporting
confidence: 88%
“…Overall this suggests that age-related deficits in the brain activity associated with memory retrieval can drive lower asymmetry in older brains. This is in line with the well-established view that aging is associated with the dedifferentiation of previously specialised neural systems (Park et al 2004(Park et al , 2012Park and McDonough 2013;Koen et al 2019), and may also reconcile well with studies demonstrating that the regionally-dependent dynamic range of activity available to older adults may be lower across varying task conditions (Garrett et al 2011(Garrett et al , 2013Kennedy et al 2017;Amlien et al 2018), a potential alternative account that may explain findings of lower-toabsent negative memory effects in older adults (Mattson et al 2014;de Chastelaine et al 2015). In particular, our finding that absent negative effects explained all instances of apparent over-activation in older adults agrees well with a similar report during retrieval (Morcom et al 2007).…”
Section: Age-related Differences In Asymmetrysupporting
confidence: 88%
“…restricting analyses to linear models when investigating the effects of age (Chen et al, 2016). In line with previous findings, visual inspection of the trajectories indicates that the HPC and ERC volumes remained stable or expanded until middle age and then declined substantially (Ziegler et al, 2012;Fjell et al, 2013;Coupé et al, 2017;Amlien et al, 2018;Li et al, 2018;Nobis et al, 2019;Langnes et al, 2020;Nyberg et al, 2021). As entorhinal cortical-hippocampal circuits are important in episodic memory processing, this pattern might partly explain the similar trajectory of age-related episodic memory deficit (Rönnlund et al, 2005;Nyberg et al, 2012).…”
Section: Differential Vulnerabilities Of Mtl Subregions In Agingsupporting
confidence: 78%
“…In further support of this, several studies have found the parietal cortex to be involved in episodic memory tasks (21)(22)(23)(24)(25). Interestingly, the lateral parietal cortex has direct anatomical connections with several key brain areas, such as the dorsolateral prefrontal cortex and the temporal cortex, and has reciprocal connections with structures in the MTLs, such as the entorhinal, parahippocampal, and hippocampal regions (23).…”
Section: Introductionmentioning
confidence: 78%